Guiding of high-intensity picosecond laser pulses in a discharge-ablated capillary waveguide - Hooker, S; Spence, D; Smith, R (Optical Society of American (OSA), 2000)
The results of a study of the channeling of intense picosecond laser pulses by a discharge-ablated capillary waveguide are presented. The peak-energy transmission for a 10-mm-long waveguide is measured to be 65% for an input intensity of 1 × 1016 W cm-2. The importance of inverse bremsstrahlung, stimulated Raman scattering, stimulated Brillouin scattering, atomic modulation instabilities, and ionization of the discharge plasma as loss mechanisms for both intense femtosecond and picosecond pulses are considered. © 2000 Optical Society of America.